THE ROLE OF PIRLS IN IMPROVING READING LITERACY IN PRIMARY EDUCATION (Ustozlar uchun, 2025)
In today’s rapidly changing world, education systems are expected to prepare students for lifelong learning. Reading literacy is essential for this purpose because it helps learners become independent and confident. For this reason, many countries carefully evaluate how well their students develop reading skills at an early age. International assessment programs are used to measure reading achievement and improve education quality. One of the most important and widely recognized programs in this field is PIRLS.